PENINGKATAN KREATIVITAS MELALUI PENDEKATAN INQUIRI DALAM PEMBELAJARAN SAINS - DWIRAHMAH, ERINA (Program Studi Magister Pendidikan Anak Usia Dini, 2013)
This study aims to determine the increase in children's creativity drawing and playingwith clay through the inquiry approach to learning science. the study involved 10 children fromkindergarten group B as the respondent. Research carried out by using the method of actionresearch spiral cyrcle model developed by Kemmis & Taggart and successfully in two cycles. datascore of the child's creativity collected through the performence of early assessment andassessment of each the end of the cycles. data score of the child's creativity improvement wasanalyzed using descriptive statistics. the results show that: (1) the creativity of drawing betweencycles has increased, which is an average score of the pre-action (span style=